Nidificación y distribución de la Torcaza Alas Blancas (Zenaida meloda) en Argentina - Vitale, Silvia; Cockle, Kristina; Bodrati, Alejandro; Ferrari, Carlos; Roesler, Ignacio; Jordan, Emilio; Ramos, Dante (Nuestras Aves, 2010)
Este artículo no cuenta con un resumen.